2000
DOI: 10.1016/s0022-5347(05)67133-9
|View full text |Cite
|
Sign up to set email alerts
|

FLEXIBLE URETEROSCOPES: A SINGLE CENTER EVALUATION OF THE DURABILITY AND FUNCTION OF THE NEW ENDOSCOPES SMALLER THAN 9Fr

Abstract: Small diameter flexible ureteroscopes are effective for diagnosing and treating upper urinary tract pathology but improved durability is required. Currently they represent a highly effective but high maintenance means of achieving retrograde access to the ureter and kidney with a need for repair after only 6 to 15 uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(55 citation statements)
references
References 9 publications
0
54
0
1
Order By: Relevance
“…4 A singlecentre evaluation of the durability of flexible ureteroscopes smaller than 9-F showed that they need repair after 6-15 uses. 20 We suggest a number of reasons 21 who concluded that it is the arduous nature of upper tract stone surgery that determines how long these scopes last. The recently described method of advancing a 200 µm laser fibre through a 2-F catheter placed in the working channel of the scopes could potentially enhance their durability.…”
Section: Discussionmentioning
confidence: 99%
“…4 A singlecentre evaluation of the durability of flexible ureteroscopes smaller than 9-F showed that they need repair after 6-15 uses. 20 We suggest a number of reasons 21 who concluded that it is the arduous nature of upper tract stone surgery that determines how long these scopes last. The recently described method of advancing a 200 µm laser fibre through a 2-F catheter placed in the working channel of the scopes could potentially enhance their durability.…”
Section: Discussionmentioning
confidence: 99%
“…There was no greater pixel loss than with the traditional ureteroscopes and the fibre-optic bundle was not replaced during the series. Previous studies reported that damage to a standard ureteroscope requiring repair occurs after 6-15 cases [18]. Pietrow et al [19] showed that certain techniques and precautions might increase ureteroscope longevity and their ureteroscopes averaged 27.5 cases before repair was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, ureteroscopy can be limited by difficult ureteric access, which can result from stricture formation, severe intravesical inflammation or extensive carcinoma in situ , previous ureteric implantation or difficulty in negotiating the prostatic median lobe in men [11]. The operational cost and particularly maintenance of the finer flexible ureteroscopes might limit the availability of this procedure [12].…”
Section: Discussionmentioning
confidence: 99%
“…MAU was used in 112 patients (mean age 38 years, range 26-57) between 1991 and 2001; the mean (range) stone size was 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)) mm, with 30 stones in the upper, 69 in the mid-and 13 in the lower ureter. In 15 patients the stones were impacted and there were signs of infection in the proximal ureter.…”
Section: Methodsmentioning
confidence: 99%